THE DIAGNOSTIC VALUE OF PROCALCITONIN FOR EARLY DETECTION OF UROSEPSIS - Nasution, M. Andriady S.; Hardjowijoto, Sunaryo; Soebadi, Doddy M.; Aryati, Aryati; Pujiraharjo, Widodo J (Indonesian Journal of Urology, 2012)
Objective: To study procalcitonin as an early and accurate marker for urosepsis. Material & Method: We performed a diagnostic study of procalcitonin, CRP and peripheral blood leucocyte in 21 patients. Patients included 12 urosepsis patients with urosepsis, and 9 trauma patients without urosepsis. This study was conducted from September 2010 to December 2010. Results: Mean and standard deviation of procalcitonin level in urosepsis patients was 27,9 ± 30,7 ng/ml, CRP was 8,9 ± 7,9 mg/l and blood leucocyte was 15125,0 ± 8969,9 mm3. Sensitivity of procalcitonin in diagnosis of urosepsis was 83,3%, specificity was 77,8%, positive predictive value was 83,3%, negative predictive value was 77,8%, positive odds ratio was 3,75 and negative odds ratio was 0,2. Diagnostic value of procalcitonin was better compared to CRP and blood leucocyte. In the receiver operating characteristics (ROC) plot, area under the curve (AUC) for procalcitonin, blood leucocyte, and CRP were 0,806 (95% CI = 0,607 – 1,004), 0,773 (95% CI = 0,568 – 0,979), and 0,602 (95% CI = 0,341 – 0,863), respectively. Conclusion: Procalcitonin is an early marker for urosepsis cases with better diagnostic value than CRP and blood leucocyte. Keywords: Urosepsis, Procalcitonin, CRP, Blood Leucocyte.